Role of "Ferritin" in COVID-19 pneumonia: Sensitive marker of inflammation, predictor of mechanical ventilation, and early marker of post-COVID-lung fibrosis - A prospective, observational, and interventional study in a tertiary care setting in India - Shital Patil; Sham Toshniwal; Abhijit Acharya; Ganesh Narwade (Wolters Kluwer Medknow Publications, 2022)
Aims and Objectives: Robust data of ferritin are available as a prognostic marker in bacterial infection and we have analyzed its usefulness in coronavirus disease 2019 (COVID-19) pneumonia in predicting severity of illness, response to treatment, and final outcome. Materials and Methods: A multicentric, prospective, observational, and interventional study included 1000 COVID-19 cases confirmed with reverse transcription-polymerase chain reaction. All cases were assessed with lung involvement documented and categorized on high-resolution computed tomography (CT) thorax, oxygen saturation, inflammatory marker, ferritin at entry point, and follow-up during hospitalization. Age, gender, comorbidity and use of BIPAP (bilevel positive airway pressure)/NIV (non-invasive ventilation) /NIV, and outcome as with or without lung fibrosis as per CT severity were key observations. Statistical analysis was done using Chi-square test. Observations and Analysis: In a study of 1000 COVID-19 pneumonia cases, age (<50 and > 50 years) and gender (male versus female) had a significant association with ferritin (P < 0.00001 and P < 0.010, respectively). CT severity score at entry point with ferritin level had a significant correlation in severity score (P < 0.00001). Ferritin level had a significant association with duration of illness (P < 0.00001). Comorbidities had a significant association with ferritin level (P < 0.00001). Ferritin level had a significant association with oxygen saturation (P < 0.00001). BIPAP/NIV during hospitalization had a significant association with ferritin level (P < 0.00001). Timing of BIPAP/NIV requirement in critical care setting had a significant association with ferritin level (P < 0.00001). Follow-up ferritin titer during hospitalization as compared to entry point normal and abnormal ferritin had a significant association in post-COVID lung fibrosis, respectively (P < 0.00001). Conclusions: Ferritin has documented very crucial role in COVID-19 pneumonia in predicting severity of illness, progression of illness and requirement of mechanical ventilation, assessing response to treatment during hospitalization. Follow up ferritin titre during hospitalization and at discharge can be used as early predictor of post-covid lung fibrosis.